The Mechanical Behavior of Self-Compacting Concrete SCC Samples Locally Produce: السلوك الميكانيكي لعينات بيتونية مصنوعة من البيتون ذاتي التوضع SCC والمنتجة محلياً - Ammar Ryad Tawashi, Soleman Alamoudi (Journal of engineering sciences and information technology, 2022)
The main objectives of this research were to obtain a locally self-compacting concrete SCC, a modern concrete with a high property, that enables it to pass and flow through the structural elements and within the steel bars under its own weight only. which was produced and tested in the reinforced concrete laboratory, using local materials in its composition. The mixtures showed no separation or accumulation of the concrete mixture, which enables us to use it in the construction, restoration and structural strengthen at the lowest costs of production.Three concrete mixtures have been produced using three grades of cement (550, 500 and 450-475 kg/m3), using three types of chemical plasticizers, which has been coded as (3500, NN, and S) and two plasticizers ratios (2%, and 2.5%) of the cement weight, verified by the experiments of the fresh properties of the concrete mixture, determination of the cylindrical strength at the age of 28 days, and the measurement of the stress-strain(ϭ, ξ) for the tested samples. It was found that the self-compacting concrete mixture with cement grade (550kg/m3) using the chemical plasticizer (3500) at (2%) ratio of cement weight, gave the best properties at a water/cement (W/C) ratio of (0.39), with relatively high concrete strength.